Inter-arm arterial pressure difference caused by prone position in the thoracic outlet syndrome patient -A case report- - Kim, Seung Su (The Korean Society of Anesthesiologists, 2010)
Thoracic outlet syndrome has neurologic symptoms caused by compression of brachial plexus, blood vessel symptoms are caused by compression of the artery or vein. The authors report a case of sudden decrease in blood pressure of the left arm after turning the patient from supine position to prone position. They confirmed that the patient had thoracic outlet syndrome after performing computed tomography.